Hawkes Bay Apple and Pear Growers' Attitudes Towards the Proposed Deregulation in the Pipfruit Industry in New Zealand - Carroll, Paul; Lockheart, Mark; Peake, Ronald; Cavana, Robert (School of Management Working Papers, 1999)
Apple and pear· growers are major stakeholders in the current debate about the proposed deregulation of the Producer Boards in New Zealand. Unfortunately there does not appear to have been any systematic attempt to find out what their attitudes are to the proposed deregulation of the Producer Boards and of the NZ Apple and Pear Marketing Board (ENZA) in particular. This study is an attempt to assess the attitudes and opinions of the Hawkes Bay apple and pear growers, who represent about 55 percent of the apple and pear growers in New Zealand. A questionnaire was developed and sent to a stratified random sample of 394 growers in the Hawkes Bay region, with an attempt to gain a representative cross section from large, medium and small growers. A total of 180 valid responses were received. These responses were analysed statistically by orchard size and the comments made by respondents were also analysed in a qualitative manner. The overall results indicated that about seventy five percent of the respondents do not support the proposed government legislation to deregulate the industry, although about 40 percent of large growers do. However, nearly 90 percent of respondents want more information, particularly about the expected financial and economic implications of the deregulation and about the experiences of overseas countries that have introduced competitive export marketing of pipfruit. The majority of small and medium sized growers were concerned that deregulation may threaten the quality of fruit exported, and result in less cost effective delivery systems and in lower returns, whereas large growers were more confident that this would not happen and they would gain from improvements in innovation and efficiency. However, a clear majority of growers (80%) support the single desk marketing approach, although over 30 percent of large growers do not. The research findings should be of particular value to the New Zealand pipfruit growers, the New Zealand Apple and Pear Marketing Board, and the Government Select Committee and departments that are currently considering issues associated with deregulating the Producer Boards.